Preserving the Cultural Heritage in Informal Settlements through Place making: The Case of Islamabad, Pakistan - Shafqat, Ramisa (Curtin University, 2021)
Using France Colony and Mehr Abadi in Islamabad, Pakistan as case studies, the thesis argues that enhanced liveability requires safeguarding the cultural heritage of rural migrants in the city. It investigates the process of organic placemaking in the two informal settlements based on mapping created through transect walks and interviews. A new policy model is suggested allowing the sustainability features embedded in the intangible cultural heritage to be recognised for improved liveability in the city.